2002
DOI: 10.1152/jn.00532.2001
|View full text |Cite
|
Sign up to set email alerts
|

Y5 Receptors Mediate Neuropeptide Y Actions at Excitatory Synapses in Area CA3 of the Mouse Hippocampus

Abstract: Neuropeptide Y (NPY) is a potent modulator of excitatory synaptic transmission and limbic seizures. NPY is abundantly expressed in the dentate gyrus and is thought to modulate hippocampal excitability via activation of presynaptic Y2 receptors (Y2R). Here we demonstrate that NPY, and commonly used Y2R-preferring (NPY(13-36)) and Y5 receptor (Y5R)-preferring ([D-Trp(32)]NPY and hPP) peptide agonists, evoke similar levels of inhibition at excitatory CA3 synapses in hippocampal slices from wild-type control mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…5C), further suggesting a role for Y 2 receptor subtype in postsynaptic NPY effects. Consistent with this, the specific Y 2 agonist NPY (1 M) (Guo et al, 2002) also induced a consistent hyperpolarization (Fig. 5A, trace 3) of 10.8 Ϯ 3.8 mV (1 M NPY 13-36 ), returning toward control levels after 5-10 min of peptide washout (n ϭ 5) (Fig.…”
Section: Direct Postsynaptic Npy Actions Via Y 1 and Y 2 Receptor Subsupporting
confidence: 76%
See 2 more Smart Citations
“…5C), further suggesting a role for Y 2 receptor subtype in postsynaptic NPY effects. Consistent with this, the specific Y 2 agonist NPY (1 M) (Guo et al, 2002) also induced a consistent hyperpolarization (Fig. 5A, trace 3) of 10.8 Ϯ 3.8 mV (1 M NPY 13-36 ), returning toward control levels after 5-10 min of peptide washout (n ϭ 5) (Fig.…”
Section: Direct Postsynaptic Npy Actions Via Y 1 and Y 2 Receptor Subsupporting
confidence: 76%
“…5C). Preincubation with BIBP3226 (1 M) did not modify 100 nM NPY 13-36 -mediated changes in membrane potential ( p Ͼ 0.05), consistent with activation of a Y 2 receptor (Guo et al, 2002).…”
Section: Direct Postsynaptic Npy Actions Via Y 1 and Y 2 Receptor Submentioning
confidence: 58%
See 1 more Smart Citation
“…This may be due not just to the hilar NPY neurons, but possibly also the NPY neurons of area CA3. Together, they potentially release NPY, which decreases glutamate release from mossy fibers [239,240]. A schematic illustration of the potential for estrogen to exert actions via BDNF and NPY.…”
Section: Discussionmentioning
confidence: 99%
“…This is also suggested by electrophysiological studies, which have shown that NPY influences mossy fiber transmission by a presynaptic mechanism [10]. Both Y2 and Y5 receptors have been implicated in these effects [15,16].…”
Section: Normal Localization Of Npy and Its Receptors In The Rat Dentmentioning
confidence: 70%